Biological pretreatment of oil palm empty fruit bunch by Schizophyllum commune ENN1 without washing and nutrient addition - Arbaain, Enis Natasha Noor; Kamal Bahrin, Ezyana; Ibrahim, Mohamad Faizal; Ando, Yoshito; Abd. Aziz, Suraini (MDPI, 2019)
Washing and drying are common steps for oil palm empty fruit bunch (OPEFB) preparation prior to pretreatment. However, the mass balance of OPEFB preparation proved a major loss of OPEFB during the washing and drying steps. An indigenous fungus, Schizophyllum commune ENN1 was used for delignification of unwashed OPEFB in biological pretreatment without nutrient addition. S. commune ENN1 achieved a maximum lignin removal of 53.8% after 14 days of biological pretreatment of unwashed OPEFB. S. commune ENN1 was able to grow on unwashed OPEFB during biological pretreatment at 55% of moisture content and 5% of oil residue. The highest amount of reducing sugars obtained from OPEFB pretreated by S. commune ENN1 was 230.4 ± 0.19 mg/g with 54% of hydrolysis yield at 96 h. In comparison, the sugar yield of OPEFB pretreated by Phanerochaete chrysosporium was 101.2 ± 0.04 mg/g. This study showed that S. commune ENN1 was feasible to remove lignin of OPEFB through biological pretreatment for enzymatic saccharification without washing and addition of nutrients.